2006
DOI: 10.4161/hv.2.2.2645
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Immunogenicity and Adsorption of a RecombinantStreptococcus pneumoniaeVaccine Antigen by an Aluminum Adjuvant

Abstract: The impact on immunogenicity of the degree of adsorption of three Streptococcus pneumoniae (Sp) vaccine antigens to aluminum adjuvants was studied. The three antigens evaluated (Sp1, Sp2 and Sp3) were highly adsorbed by aluminum hydroxide adjuvant, but not adsorbed by aluminum phosphate adjuvant. All of the Sp antigens adjuvanted with aluminum hydroxide elicited higher antibody responses in mice than formulations prepared with aluminum phosphate or non-adjuvanted antigen. Varying the percent aluminum-bound Sp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Berthold et al [34] concluded that adsorption of recombinant anthrax protective antigen to aluminum phosphate enhances the immunogenicity of lower doses of antigen. Levesque et al [35] also concluded that increased adsorption to adjuvant correlates with greater antigenicity of the proteins studied.…”
Section: Discussionmentioning
confidence: 95%
“…Berthold et al [34] concluded that adsorption of recombinant anthrax protective antigen to aluminum phosphate enhances the immunogenicity of lower doses of antigen. Levesque et al [35] also concluded that increased adsorption to adjuvant correlates with greater antigenicity of the proteins studied.…”
Section: Discussionmentioning
confidence: 95%
“…We then compared vaccine formulations with AH, with fully adsorbed L1V (with or without CpG), to vaccine formulations with phosphate-buffer treated aluminum hydroxide (PTAH), which did not significantly adsorb L1V. Similar to other studies that investigated the immune response to adsorbed antigens like recombinant protective antigen from anthrax [11] or recombinant antigens from Streptococcus pneumonia [37], we too consistently found that the L1V antigen adsorbed to an aluminum salt gave enhanced antibody-responses and better protection after VACV-challenge when compared to formulations that had L1V free in solution in the presence of AH (i.e., unbound LIV). The mechanism of why L1V gives enhanced antibody responses when adsorbed to AH is not known and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This conformational destabilization was seen previously for some model protein antigens [38, 39], but antibody responses were not ascertained. Alternatively, Levesque et al hypothesized that the differences in antibody responses that they saw with recombinant antigens from Streptococcus pneumonia may have been due to initially higher localized concentration of antigen in proximity with adjuvant when antigen was adsorbed to AH [37]. …”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of action is an area of ongoing research but the major contribution to adjuvanticity is the depot effect of antigen (Ag) adsorbed to the adjuvant, that is stored for an extended time at the site of injection and is thus available at comparatively high concentrations for uptake by phagocytic cells (Guy, 2007; Harrison, 1935). Activation and recruitment of antigen-presenting cells, which play a key role in the amplification and differentiation of antigen-specific T-cells, also explain the immunological phenomena triggered by alum (Levesque et al, 2006). …”
Section: Influenza Vaccines Strategiesmentioning
confidence: 99%